Penerapan Pendekatan Manual Dexterity Untuk Meningkatkan Keaktifan Siswa Kelas IV SD Negeri 0501 Hutanopan - Siti Asrina Harahap; Mancar Mancar; Lina Maya Sari Siregar (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
The aim of this research is to determine the application of learning in class IV of SD Negeri 0501 Hutanopan using a manual dexterity approach to student activity. The type of research used is classroom action research. Based on the research results, it can be concluded that in cycle I an increase in student learning activity had occurred but was not optimal. However, in cycle II there was quite a good improvement until it reached the completeness expected by the researchers. Increased student learning activity, namely in the pre-cycle student activity in the "Good" category, there was only 1 indicator or 7%. In cycle I, student activity in the "Good" category had 4 indicators or 27%. In cycle II, student activity in the "Good" category had 12 indicators or 80%. So it can be concluded that using the manual dexterity approach can increase the learning activity of students in class IV of SD Negeri 0501 Hutanopan, Lubuk Barumun District, Padang Lawas Regency.